Effect of storage time and different mineral forms on vitamin stability - Süleyman Tekelioğlu; Emel Gürbüz; Behiç Coşkun; Fatma İnal (Eurasian Journal of Veterinary Sciences)
Aim: This research was made to determine the effect of storage time and inorganic and organic minerals on vitamin stability in vitamin-mineral premixes. Materials and Methods: In experiment, groups were divided into three main groups for determination vitamin stability. Groups consist of control, organic trace minerals and inorganic trace minerals. Premixes were stored for one year and vitamin A, E, K, C, thiamine and niacin analyses were made for determination vitamin stability. Results: Vitamin stability was lower in inorganic minerals group than the control and organic mineral groups. There were statistically difference (p<0.05) in vitamin stability for vitamin K from second month, for vitamin A, C, thiamine from fourth month and for vitamin E and niacin from ninth month. Conclusion: The use of inorganic forms of mineral in vitamin-mineral premixes show a negative effect on the vitamin stability. The use of organic forms of minerals will help protect the vitamin stability.